The beginning of everything : a novel - Fraser, Jackie, 1972- (Dell, 2023)
"After escaping a bad relationship, Jess Cavendish is running and leaving it all behind, carrying just a few treasured belongings in her rucksack. She needs to start over, but that means sleeping where she can and making the most of her slim savings. Luckily, she comes across a recently sold, unoccupied house. It couldn't hurt to stay while she saves up enough to get her own place, right? Gethin Thomas is also looking for a fresh start. He's moved back to his hometown after the end of a long-term relationship, anxious to move into the fixer-upper he bought and out of his sister's cramped guest room. When he walks through the door one morning, he finds Jess, who's ready to run again, and surprises them both by offering to let her stay. It feels like the right thing to do, but Jess doesn't want a handout. They strike a bargain: Jess will help with the renovation, furnishing, and decorating in exchange for room and board. While they peel wallpaper and shop for new furniture, an unexpected friendship develops as they bond over music and food, each slowly opening up about their pasts. And when it's time for Gethin to move in, he convinces Jess to be his official housemate and she agrees--so long as he lets her pay rent. Before long, the connection between them shifts to an attraction that seems both inevitable and overwhelming, and Jess must decide what she wants for her future. With so much hurt in her past, can she risk loving again? She was brave enough to reach for a new life--and now a future she hadn't even dreams possible could be just within her grasp"--